USE OF BOTANICAL INSECTICIDES AS AN ALTERNATIVE FOR THE MANAGEMENT OF THE MEXICAN BEAN WEEVIL - Silva, Karen Ferreira Da; Baldin, Edson Luiz Lopes; Pannuti, Luiz Eduardo Da Rocha (Universidade Federal Rural do Semi-Árido, 2016)
ABSTRACT: This study aimed to evaluate the insecticidal activity of eight botanical species in the behavior and biological development of Zabrotes subfasciatus (Coleoptera: Chrysomelidae: Bruchinae) under laboratory conditions. The botanical species were applied on bean grains (Phaseolus vulgaris Linnaeus) directly as powder or indirectly within TNT bags. Three laboratory assays were performed. First, a repellent activity test was performed by exposing twenty couples of Z. subfasciatus adults in a choice-test arena. Second, a mortality test was performed for seven days after infestation. Finally, the oviposition and emergency rates of adults (%) and the development from egg to adult (in days) were evaluated in seven couples (males and females) for seven days inside of a vial containing 0.3g of the powder from each botanical species and 10 g of bean grains (3% w.w-1). The study was conducted in a completely randomized design, and the treatments were arranged as a factorial design (2 x 9) with two factors (factor 1= powder and TNT bag application forms and factor 2= eight botanical species and control) with eight replications. The powder application form was more efficient in controlling Z. subfasciatus. Azadirachta indica (powder application), Ruta graveolens (powder application), and Piper aduncum (TNT bag) reduced the infestation of adults. The species A. inidica, Piper tuberculatum, Trichilia catigua, Pfaffia glomerata, R. graveolens, and Mentha pulegium inhibited the oviposition of the insects regardless of the formulation applied. R. graveolens (powder application) caused 100% of mortality. The powder application of R. graveolens and M. pulegium reduced egg viability and insect emergence; therefore, they are very promising alternatives to control Z. subfasciatus in stored grains.

RESUMO: O objetivo do trabalho foi avaliar o efeito de pós de oito espécies botânicas, misturados aos grãos de feijão, Phaseolus vulgaris (Fabaceae), ou em sachês, sobre os aspectos comportamentais e de desenvolvimento biológico de Zabrotes subfasciatus (Coleoptera: Chrysomelidae: Bruchinae) em laboratório. Três ensaios foram realizados. Primeiro, a repelência de adultos de Z. subfasciatus pelas espécies vegetais foi avaliada com 20 casais em teste com chance de escolha. Segundo, a mortalidade de adultos foi avaliada, diariamente, até o sétimo dia após a infestação. Terceiro, sete casais foram mantidos por sete dias em recipientes contendo 0,3 g de pó de cada espécie vegetal e 10 g de grãos de feijão (3% p.p-1) para avaliação dos parâmetros oviposição, emergência de adultos (%) e período de desenvolvimento ovo-adulto (dias) de Z. subfasciatus. Os ensaios seguiram arranjo fatorial 2 x 9 (fator 1 = formas de aplicação pó e sachê; fator 2 = oito espécies vegetais e testemunha) em delineamento inteiramente casualizado com oito repetições. A forma de pó foi mais eficiente no controle de Z. subfasciatus. As espécies Azadirachta indica (na forma de pó), Ruta graveolens (na forma de pó) e Piper aduncum (na forma de sachê) reduziram a infestação por adultos do inseto. A. indica, Piper tuberculatum, Trichilia catigua, Pfaffia glomerata, R. graveolens e Mentha pulegium, independente da forma de aplicação utilizada, inibiram a oviposição do inseto. R. graveolens (na forma de pó) controlou 100% de adultos. Pós das espécies R. graveolens e M. pulegium reduziram a viabilidade de ovos e emergência do inseto, apresentando alto potencial no controle alternativo de Z. subfasciatus em feijão armazenado.
INSETICIDAS VEGETAIS COMO ALTERNATIVA PARA O MANEJO DO CARUNCHO-DO-FEIJÃO
Keywords: Bruchinae; Chrysomelidae; Zabrotes subfasciatus; Bruchinae; Chrysomelidae; Zabrotes subfasciatus